At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Solve the system by substitution.
y = 3x – 2
y = 4x


Sagot :

Answer:

x = -2

y = -8

Step-by-step explanation:

y = 3x – 2

y = 4x

Substituting the second equation for y into the first

4x = 3x - 2

Subtract 3x from both sides

x = -2

plug in x = -2 into the second equation

y = 4(-2)

y = -8